Standing in My Way Nine to Five : Investigating Bullying Behaviours Prevalent Among IT Professionals in India - Trivedi, Vaishali; Agarwala, Tanuja (Prabandhan: Indian Journal of Management, 2021)
In modern workplaces, competition between employees is a significant determinant of career progress. Hence, employees are likely to engage in a range of negative behaviors to outperform each other. The present exploratory study attempted to identify specific bullying behaviors prevalent in the Information Technology (IT) sector and explained bullying from a sociocultural perspective. A questionnaire survey was conducted among 222 IT professionals to explore workplace bullying prevalence and examine underlying workplace bullying behaviors. Based on the responses to the Negative Acts Questionnaire-R, it emerged that 44.13% of the respondents had experienced some form of bullying at their workplace, and 19.8% reported moderate to severe levels of bullying. Exploratory factor analysis identified four types of bullying behavior : Attacking Self-Esteem, Work Surveillance, Threatening Situations, and Obstructing Competence. The results revealed that Obstructing Competence and Attacking Self-Esteem were the most prevalent types of bullying behaviors among IT professionals in India. The findings of the study were discussed from a sociocultural perspective within the context of working norms of the IT sector in India. The implications for managing negative acts in the IT sector were also discussed.